KONTRIBUSI SEKTOR PERTANIAN DALAM PENYEDIAAN LAPANGAN KERJA DAN PERBANDINGANNYA DENGAN SEKTOR-SEKTOR LAIN - AMIRUDDIN SYAM; KHAIRINA M. NOEKMAN (SOCA: Jurnal Sosial Ekonomi Pertanian, 2002)
The objective of the study is to assess the performance of labor force bysector. It followed by the comparison among sectors. The study found that: (1) Thelabor force absorption role between 1985-1989, dominated by agricultural sectorwhich was 56.66% of all other sector absorption rate were only 5 – 13%, (2) In theshorterm, the labor force absorption rate of services and agricultural sectors are notas. Persistent as industrial and trade sectors. However, in the long run, theabsorption rate of agricultural sectors are persistently compared to industry andtrade, (3) Agricultural sectors are relatively more stable in the absorption of laborforce compared to other sectors.